"A Town Should Be Built to Make the Whole Thing Work": Modeling Patterson, City Beautiful of California's Central Valley. (May 2015) - Ekman, Peter
Patterson Colony, an agricultural town built out at the height of the City Beautiful era, exhibits that movement's distinctive monumental geometries writ small, imitative of Washington, D.C., and jarringly unlike its grid-bound neighbors in California's Central Valley. The story of Patterson's street plan sheds light on an unfamiliar site and scale of comprehensive planning, and shows how the beautifiers' rhetorics could be recoded and harnessed to a speculative real-estate venture. In Patterson we see these tropes—"order" in particular—taking on complex valences that are at once aesthetic and technical, revising any hard-and-fast distinction between City Beautiful and City Practical imaginaries. This history, finally, allows us to rethink how replicable urban forms travel, and to specify the meanings, uses, and predicates of self-appointed "model" towns—a designation that has been attached, sometimes incautiously, to countless episodes in the evolution of the American city and suburb.